Antara Aqidah dan Akhlak dalam Pendidikan Islam: Suatu Tinjauan Kritis - Nurul Ainin, Dewi Zulianah; Dewi Zulianah (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2021)
The existence of material content in Islamic education is very diverse and complex. One of them is about aqidah and morality. The common understanding related to aqidah move in the realm of theology, faith, and piety. While morality dwells in the realm of student character formation. The main task of educational institutions is to form a superior personality, design to promote social sensitivity, and instill the importance of morality. The urgency in Islamic education in developing an understanding of how the importance of the separation between moral beliefs and aims to provide an overview of how the conception that was carried in the charge of material in the learning process. Furthermore, the complexity of understanding is once again aiming to give answers in preventive linked to the wave of modernity that is upon the world of Islamic education Keywords: Aqidah, Morality, Modernity, Preventive Action, Islamic Education